2014
DOI: 10.1021/ph500159g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroad Bandwidth and Highly Sensitive Optical Ultrasonic Detector for Photoacoustic Imaging

Abstract: We demonstrate an ultrasonic detector with unprecedented broad bandwidth and high sensitivity, based on an imprinted polymer optical microring. It has an acoustic response of up to 350 MHz at −3 dB and noise-limited detectable pressure as low as 105 Pa in this frequency range. Application of such a detector in photoacoustic imaging leads to improved axial resolving ability compared with using the conventional ultrasound detector, and sub-3 μm axial resolution is achieved, which is more than a 2-fold improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 37 publications
0
93
0
Order By: Relevance
“…Micro-ring resonator has been demonstrated as a high-performance ultrasound detector with both broad bandwidth and great detection sensitivity. Our previous studies have shown that the micro-ring detector has an intrinsic acoustic response from nearly DC up to 350MHz at −3dB [22], and a noise equivalent detectable pressure over this bandwidth as low as 105 Pa. This sensitivity is comparable to or even better than those of conventional piezoelectric transducers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Micro-ring resonator has been demonstrated as a high-performance ultrasound detector with both broad bandwidth and great detection sensitivity. Our previous studies have shown that the micro-ring detector has an intrinsic acoustic response from nearly DC up to 350MHz at −3dB [22], and a noise equivalent detectable pressure over this bandwidth as low as 105 Pa. This sensitivity is comparable to or even better than those of conventional piezoelectric transducers.…”
Section: Introductionmentioning
confidence: 94%
“…Micro-ring has been utilized in highresolution PA imaging [27,28], as well as real-time THz pulse detection [29]. The device has demonstrated an ultra-broadband intrinsic frequency response from nearly DC to 350 MHz at −3dB [22]. However, the whole system response bandwidth is not only limited by the bandwidth of the photodetector but also by the duration of the laser pulses.…”
Section: Principlesmentioning
confidence: 99%
“…38 Chen et al used polymer micro-ring resonator as a PA signal detection system, the detection bandwidth up to 90 MHz, to achieve highresolution imaging of biological tissue. [39][40][41] In order to achieve the noncontact detection of ultrasonic signals, Wang Yi et al employed the low coherence Michelson interferometer (the detection bandwidth up to 17 MHz) achieving noncontact PA signal detection. 28 In 2012, Cedric Blatter adopted phasesensitive optical coherence tomography system to realize the noncontact measurements of PA signals (the bandwidth of 13 MHz), and acquired PA and OCT images of simulated samples.…”
Section: All-optical Pa Detectionmentioning
confidence: 99%
“…While broad-band detection can be achieved with polyvinylidene-fluorid-based (PVDF) hydrophones, for the most sensitive PZT transducers, the BW is typically on the same order of magnitude as the center frequency, resulting in narrow bandwidths, especially if highly sensitive detection of frequencies below 10 MHz is required. In photoacoustic imaging, artifacts are created by the simultaneous detection of small and large structures, where both high-and low-frequency spectral components are integrated for image reconstruction [8,9]. Therefore, a sensor with a high sensitivity to low-and high-frequency spectral components would be best suited for PAI.…”
Section: Introductionmentioning
confidence: 99%